2013
DOI: 10.1111/acps.12090
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acute tryptophan depletion on attentional performance in adult patients with ADHD

Abstract: The present preliminary results are indicative of the contribution of serotonergic neurotransmission to attentional processes in adults with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 65 publications
1
47
0
6
Order By: Relevance
“…More recent studies demonstrate an inverse relationship between trait impulsivity and the acute tryptophan depletion effect on reactive aggression after low provocation in patients with adolescent and adult ADHD (Kotting et al 2013; Zimmermann et al 2012). While there seems to be a relationship between acute tryptophan depletion and attentional performance in adult patients with ADHD (Mette et al 2013), there is no such effect on verbal declarative memory in young patients with ADHD (Zepf et al 2013) and on processing affective prosody in male adults with ADHD (Grabemann et al 2013). …”
Section: Functional Neurochemistry Of Neurotransmitter Circuitry Systmentioning
confidence: 99%
“…More recent studies demonstrate an inverse relationship between trait impulsivity and the acute tryptophan depletion effect on reactive aggression after low provocation in patients with adolescent and adult ADHD (Kotting et al 2013; Zimmermann et al 2012). While there seems to be a relationship between acute tryptophan depletion and attentional performance in adult patients with ADHD (Mette et al 2013), there is no such effect on verbal declarative memory in young patients with ADHD (Zepf et al 2013) and on processing affective prosody in male adults with ADHD (Grabemann et al 2013). …”
Section: Functional Neurochemistry Of Neurotransmitter Circuitry Systmentioning
confidence: 99%
“…Tryptophan depletion, which causes reduction in brain 5-HT synthesis was found to impact aggression (vanPolier et al, 2014, Kotting et al, 2013, Zimmerman et al, 2013, Stadler et al, 2007 inattention (Zepf et al, 2010, Mette et al, 2013, behavioral inhibition , impulsivity domains of ADHD. We have summarized findings on tryptophan depletion effects and ADHD in Table 2.…”
Section: Tryptophan Depletion Studies In Adhdmentioning
confidence: 99%
“…The impact of acute tryptophan depletion (ATD) on attention performance of adult male ADHD patients has been studied by orally administering a tryptophan-free amino acid mixture and carrying out a continuous performance test in the ATD group as well as control group on tryptophan balanced diet. Following a double blind study design it has been reported in ADHD-ATD group target/non-target discrimination ability and sustained attention is affected, which indicates that 5-HT neurotransmission is related to attention processing in adult ADHD (Mette et al, 2013).…”
Section: Inattentionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent issue of Acta Psychiatrica Scandinavica included four papers that employed the acute tryptophan depletion (ATD) technique in patients (1)(2)(3)(4). These studies provided interesting insight into how low serotonin synthesis might influence measures of cognition, attention and aggression in young and adult patients with attention deficit hyperactivity disorder (ADHD).…”
mentioning
confidence: 99%